PENDAHULUAN PELATIHAN PEMBUATAN KERIPIK KELAPA UNTUK UMKM DI DESA LEGUNG BARAT: pelatihan, kelapa, kripik kelapa, nilai tambah - legung barat, ubay (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The purpose of this training is to improve the community's knowledge and skills in processing coconuts into high-value processed products, particularly crispy coconut chips. Although coconuts are only used for conventional products such as coconut milk and oil, this commodity is easily found in many places. The method of processing coconuts into crispy, long-lasting chips and product marketing strategies to maintain market competitiveness were taught to participants in this training. Theoretical explanations, live demonstrations, and practical coconut chip making were part of the training method. The training results showed that participants had a better understanding of the production process, equipment usage, and the economic potential of coconut chip products. It is hoped that this training will help build small businesses based on local potential and encourage community economic independence.